2011
DOI: 10.1371/journal.pone.0014697
|View full text |Cite
|
Sign up to set email alerts
|

ENCODE Tiling Array Analysis Identifies Differentially Expressed Annotated and Novel 5′ Capped RNAs in Hepatitis C Infected Liver

Abstract: Microarray studies of chronic hepatitis C infection have provided valuable information regarding the host response to viral infection. However, recent studies of the human transcriptome indicate pervasive transcription in previously unannotated regions of the genome and that many RNA transcripts have short or lack 3′ poly(A) ends. We hypothesized that using ENCODE tiling arrays (1% of the genome) in combination with affinity purifying Pol II RNAs by their unique 5′ m7GpppN cap would identify previously undescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…It will be of interest to determine the similarities and differences in gene expression of acutely HCV infected proliferative and growth arrested differentiated human hepatoma-derived cells [36]. In comparison with our reported ENCODE tilling array (interrogates 1% of the human genome) analysis of HCV infected cirrhotic liver that identified 95 differentially expressed genes as compared to controls, our current analysis of acutely infected hepatoma cells showed that 20% of these genes were also differentially expressed [14]. This is a relatively large percentage of overlap since liver represents a much more complex transcriptome due to the presences of a number of other cell types besides hepatocytes and the fact that the ENCODE analysis was of chronically infected cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be of interest to determine the similarities and differences in gene expression of acutely HCV infected proliferative and growth arrested differentiated human hepatoma-derived cells [36]. In comparison with our reported ENCODE tilling array (interrogates 1% of the human genome) analysis of HCV infected cirrhotic liver that identified 95 differentially expressed genes as compared to controls, our current analysis of acutely infected hepatoma cells showed that 20% of these genes were also differentially expressed [14]. This is a relatively large percentage of overlap since liver represents a much more complex transcriptome due to the presences of a number of other cell types besides hepatocytes and the fact that the ENCODE analysis was of chronically infected cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously that the analysis of 5' capped RNA, rather than poly(A) selected RNA, provides a more sensitive means of detecting differentially expressed genes in HCV infected biospecimens [14]. Our approach purifies Pol II transcripts by binding their 5' caps with a high-affinity variant of the RNA cap binding protein (eIF4E K119A ), enabling us to isolate and study transcripts with short or missing 3' poly(A) ends [12,13,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated using TRIzol (Invitrogen) and quality of RNA assessed by an Agilent 2000 bioanalyzer as described previously (21,23,24). RNA sequencing was performed on 86 individual colon samples: 21 SSA/Ps (12 syndromic and 9 sporadic), 10 hyperplastic polyps, 10 adenomatous polyps, 21 uninvolved colon, 20 control colon, and 4 colon cancer samples.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, TRIM22 expression is significantly upregulated during clearance of hepatitis C virus (HCV) in chimpanzees [52]. These findings are paralleled in human infections, as TRIM22 is significantly upregulated in cirrhotic liver from HCV patients and patients with mild chronic HCV infection and no fibrosis [53]. Further research is needed to assess the role of TRIM22 in inhibiting HBV and HCV in vivo .…”
Section: Biological Functions Of Trim22mentioning
confidence: 99%